Water characteristic curve and shear strength of soil with bimodal characteristics - Priono (2013)
Rainfall-induced slope failures frequently occur around the world. One of the controlling parameters in slope stability assessment is shear strength of soil. Shear strength of soil is usually affected by soil-water characteristic curve (SWCC). Existing SWCC and shear strength models are for soils with unimodal characteristics, but not for soils with bimodal characteristics. [2nd Award]